A study of head and neck space infections and their sensitivity pattern at tertiary care hospital - Jindal, Simmi; Parmar, Suchina; Davessar, Jailal; Bawa, A. G. S.; Singh, Gurbax; Prinja, Sumit; Bali, Alisha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Head and neck space infections including submandibular, buccal, diffuse neck space, peritonsillar, parapharyngeal, parotid, submental, retropharyngeal, result in frequent hospital visits. Infection can be mild or severe life threatening infection. Methods: 40 patients with head and neck space infections were considered. Pus samples were collected with aseptic precautions and sent to department of microbiology for culture and antibiotic sensitivity. Results: The most common head and neck space infections are submandibular followed by buccal, diffuse neck abscess, peritonsillar, parapharyngeal, parotid, submental and retropharyngeal. Incidence of aerobic growth is 60%, fungal 10%, anaerobic 7.5%, tubercular 7.5% and no growth 15%. Predominant aerobes are Staphylococcus aureus, Pseudomonas aeruginosa, Methicillin Resistant Staphlococcus aureus, Klebsiella species and anaerobes are Peptostreptococcus and bacteroides and fungal species is Candida. Aerobic organism showed maximum sensitivity to Amikacin, Vancomycin, Linezolid, Piperacillin+Tazobactum, Clindamycin, Erythromycin, Cefoperazone, Ceftriaxone and maximum resistant to Levofloxacin, Cefoperazone, Ceftriaxone, Meropenem. Anaerobic bacteria showed sensitivity to Clindamycin, Metronidazole and Colistin and resistance to Vancomycin. Conclusions: Bacteriological examination and culture of head and neck abscesses helps to identify causative organisms. It helps to isolate even rarest of organisms and by knowing their sensitivity pattern we can detect specific therapy against them. Thus it helps in more effective treatment and fast recovery.